2020
DOI: 10.3390/c6030051
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cellulose Nanocrystals on the Coating of Chitosan Nanocomposite Film Using Plasma-Mediated Deposition of Amorphous Hydrogenated Carbon (a–C:H) Layers

Abstract: The substitution of petroleum-based polymers with naturally derived biopolymers may be a good alternative for the conservation of natural fossil resources and the alleviation of pollution and waste disposal problems. However, in order to be used in a wide range of applications, some biopolymers’ properties should be enhanced. In this study, biocompatible, non-toxic, and biodegradable chitosan (CS) film and CS reinforced with 10 wt% of cellulose nanocrystals (CN–CS) were coated with amorphous hydrogenated carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Afterwards, the ascending layer thicknesses were recorded in order to determine the pure changes of the surface bonds through the a-C:H coating. The evaluation of the spectra was done on the basics of infrared spectroscopy [ 31 ] and based on previous results and the work of other groups [ 11 , 12 , 13 , 16 , 48 , 49 , 50 , 51 , 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Afterwards, the ascending layer thicknesses were recorded in order to determine the pure changes of the surface bonds through the a-C:H coating. The evaluation of the spectra was done on the basics of infrared spectroscopy [ 31 ] and based on previous results and the work of other groups [ 11 , 12 , 13 , 16 , 48 , 49 , 50 , 51 , 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…The valence state, stereochemistry and electronic configuration of the central atom can be obtained by X-ray absorption near-edge structure spectroscopy (XANES) [65]. Schlebrowski et al [66] reported that near-edge X-ray absorption fine structure (NEXAFS) was used to determine the binding state of surface carbon atoms.…”
Section: Characterization Of Graphene-based Nanocompositesmentioning
confidence: 99%